Acute Myocardial Infarction: Changes in Patient Characteristics, Management, and 6-Month Outcomes Over a Period of 20 Years in the FAST-MI Program (French Registry of Acute ST-Elevation or Non-ST-Elevation Myocardial Infarction) 1995 to 2015. Issue 20 (14th November 2017) - Puymirat, Etienne; Simon, Tabassome; Cayla, Guillaume; Cottin, Yves; Elbaz, Meyer; Coste, Pierre; Lemesle, Gilles; Motreff, Pascal; Popovic, Batric; Khalife, Khalife; Labèque, Jean-Noel; Perret, Thibaut; et al.
Abstract : Background: ST-segment–elevation myocardial infarction (STEMI) and non–ST-segment–elevation myocardial infarction (NSTEMI) management has evolved considerably over the past 2 decades. Little information on mortality trends in the most recent years is available. We assessed trends in characteristics, treatments, and outcomes for acute myocardial infarction in France between 1995 and 2015. Methods: We used data from 5 one-month registries, conducted 5 years apart, from 1995 to 2015, including 14 423 patients with acute myocardial infarction (59% STEMI) admitted to cardiac intensive care units in metropolitan France. Results: From 1995 to 2015, mean age decreased from 66±14 to 63±14 years in patients with STEMI; it remained stable (68±14 years) in patients with NSTEMI, whereas diabetes mellitus, obesity, and hypertension increased. At the acute stage, intended primary percutaneous coronary intervention increased from 12% (1995) to 76% (2015) in patients with STEMI. In patients with NSTEMI, percutaneous coronary intervention ⩽72 hours from admission increased from 9% (1995) to 60% (2015). Six-month mortality consistently decreased in patients with STEMI from 17.2% in 1995 to 6.9% in 2010 and 5.3% in 2015; it decreased from 17.2% to 6.9% in 2010 and 6.3% in 2015 in patients with NSTEMI. Mortality still decreased after 2010 in patients with STEMI without reperfusion therapy, whereas no further mortality gain was found in patients with STEMI with reperfusion therapy or in patients with NSTEMI, whether or not they were treated with percutaneous coronary intervention. Conclusions: Over the past 20 years, 6-month mortality after acute myocardial infarction has decreased considerably for patients with STEMI and NSTEMI. Mortality figures continued to decline in patients with STEMI until 2015, whereas mortality in patients with NSTEMI appears stable since 2010. Abstract : Supplemental Digital Content is available in the text.